Measurements of Surge Currents and Potentials in a Radio Base Station for Estimation of Lightning Threat - Markowska, R.; Wiater, J.; Sowa, A. (Elektronika ir Elektrotechnika, 2011)
The paper presents a methodology and example results of on-site measurements of surge current flows and potentials in a radio base station. The basic idea of the method is to simulate a lightning strike to the base station tower using a surge generator and to measure surge current flows and potentials with respect to remote ground at various elements of the station. The aim of the experiment was to provide complex information on the performance of a radio base station affected by surge currents. This information will be used in further theoretical analysis of lightning threat for testing and verification of numerical models and/or for analysis of various lightning protection measures.